Spatial Competition with Entry Deterrence considering Horizontal Product Differentiations - Ai-nong Zhou (Journal of Applied Mathematics)
Spatial competition plays important roles in economics, which attracts extensive research. This paper addresses spatial competitions along with horizontal product differentiations and entry deterrence. By the dynamic game theory model about one firm and a potential entrant with different cost in a linear city, this paper finds that both the higher fixed setup cost and the higher transportation cost deter entrants. To efficiently deter the entrants, the establisher is inclined to locating at the middle point of the linear city.